Mapping the research, policy, and clinical management landscape of post-tuberculosis lung disease: A scoping review - Yochanan Hoppenstein; Olena Ivanova; Salome Charalambous (PLOS Global Public Health, 2026)
Tuberculosis (TB) can result in debilitating long-term health consequences, most notably post-tuberculosis lung disease (PTLD). However, these conditions remain insufficiently integrated into global policy and routine care, contributing to fragmented care for millions of TB survivors. This scoping review maps the current landscape to identify critical gaps and support the harmonisation of research, policy, and practice. We conducted a scoping review of peer-reviewed research and global guidance documents published between June 2017 and May 2025. The search for peer-reviewed research focused specifically on PTLD management, whereas the search for guidance documents used broader terms for post-tuberculosis (post-TB) sequelae to assess how PTLD is conceptualised within the wider policy context. Data on recognition, management recommendations, and classification were systematically extracted and thematically synthesised. We included 28 documents: 14 research publications and 14 global guidance documents. The research literature offered detailed management content, including diagnostic assessment, pulmonary rehabilitation and chronic care approaches, acute-on-chronic complication management, and follow-up schedules. In contrast, only 8 of 14 guidance documents provided management recommendations relevant to PTLD. Recurring guidance recommendations included structured post-TB respiratory assessment, multidisciplinary care incorporating rehabilitation and psychosocial support, and clinical, radiological, and functional follow-up, whereas acute-on-chronic management was addressed far less consistently. Overall, we found a translation gap between evidence generation in research and its operationalisation in global guidance. Despite growing awareness and some recent policy progress, the global response to PTLD remains hampered by inconsistent and incompletely operationalised guidance, as well as the absence of standardised definitions, classification, and programmatic indicators. Accelerating the translation of research into integrated policy and practice is needed to improve the long-term health and quality of life of TB survivors.